La colonisation militaire en Phrygie (IVe siècle avant-IIIe siècle après J.-C.). Tome 1 : synthèse Dynamiques spatiales, économiques et sociales - Roux, Michel (Histoire & Épigraphie, 2023)
At the heart of a geographically ill-defined Phrygian space during Antiquity, the installation of military settlers, former soldiers and troupiers still in operation, met perfectly identified strategic objectives fromthe Achaemenids, the Hellenistic monarchs or the Romans. It was to control a space essential for terrestrial communications between the interior of the Anatolian plateau on the one hand and the Aegean on the other, but also between this same coast and Cilicia, and then beyond Syria. On a tactical level, this military presence was to protect Phrygian plateau and valleys from the lust of poorly controlled neighboring populations like Pisidians. Basedon numerous archaeological, numismatic and epigraphic sources, examining each community on a case-by-case basis, this work studies the consequences of the installation of these soldiers on the local reality, whether at the economic level, cultural, religious or social. Covering a long period from the 4th century BC to the end of the Severan Dynasty, he endeavours to weigh the evolutions related to the presence of these alien soldiers. Between the Achemenid Phrygia and the Hellenistic and then Roman one, the aspect of the region, essentially rural at the outset, has gradually evolved: from the Hellenistic era, we observe an important phenomenon of poliadization, making the communication network more dense and the control of local populations more complex.